Connecting to Compete 2023: Trade Logistics in the Global Economy. The Logistics Perfomance Index and Its Indicators - Arvis Jean-François; Ojala Lauri; Shepherd Ben; Ulybina Daria; Wiederer Christina (The World Bank, 2025)
The 7th edition of Connecting to Compete, a report summarizing the findings from the new dataset for the Logistics Performance Index (LPI) and its component indicators. The 2023 LPI encapsulates the firsthand knowledge of movers of international trade and evidence from supply chain tracking data.
This information is relevant for policymakers and the private sector seeking to identify reform priorities for trade and logistics infrastructure. Findings include:
• Notwithstanding the pandemic-induced disruptions to shipping and the global supply chain crisis, average overall scores in the LPI 2023 were roughly the same as in the last survey in 2018.
• The new indicators point to widespread differences in delays and supply chain reliability across the World. Several countries experience much larger delays than advanced and emerging economies. Binding constraints for low performances may be traced to infrastructure, productivity, or clearance procedures.
• The survey confirms growing demand for green logistics options, which lessen the carbon footprint of supply chains and keep trade moving.